Nodal Solutions for Some Second-Order Semipositone Integral Boundary Value Problems - Huiqin Lu; Yang Wang; Yansheng Liu (Abstract and Applied Analysis)
Using bifurcation techniques, we first prove a global bifurcation theorem for nonlinear second-order semipositone integral boundary value problems. Then the existence and multiplicity of nodal solutions of the above problems are obtained. Finally, an example is worked out to illustrate our main results.